“NEW NORMAL” SEBAGAI MOMENTUM KEBANGKITAN EKOWISATA: Sebuah Kajian Awal tentang Daya Dukung Lingkungan Pascapandemi Covid-19 - Andreas Rudiyanto; Eko Sugiarto (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2020)
Covid-19 pandemic has changed many things in life. One that is quite prominent is the behavior changing. The term "new normal" then became very popular. Many equations of this term appear in Bahasa Indonesia, such as “kenormalan baru”, “normal baru”, “tatanan kehidupan baru”, and many more which all refer to "a new normal condition". These new normal conditions include (1) wearing a mask when leaving the house or interacting with other people whose health status is unknown; (2) washing hands using soap with running water or using an alcohol-based antiseptic liquid / hand-sanitizer; (3) keep a one-meter minimum distance from other people and avoid a group of people, crowd, and crammed into a public space; and (4) increase endurance by implementing clean and healthy living behaviors. Keeping a one-meter minimum distance from other people and avoiding a group of people, crowd, and crammed into a public space is a discussion of carrying capacity of tourism discussed in this article. Thus, the purpose of this writing is to provide a perspective about an implementing concept of carrying capacity in tourism destinations after the Covid-19 pandemic. The method used in collecting data in this study is a literature review on documents that discuss the "new normal" and ecotourism associated with current conditions. Based on the results of those kinds of literature, the author concludes that "new normal" is a condition that can be used as a momentum for the rise of ecotourism, especially related to the implementation of the concept of carrying capacity in tourism destinations.